The transition from moderately thick shells to thick shells of general shape by using finite element analysis - Ozkul, Tulay Aksu; Kara, Nail; Kumbasar, Nahit (Elsevier BV, 2007)
Two types of shell bending elements are presented for the analysis of both moderately thick and thick shells of general shape. The first is a 2-D curved trapezoidal finite element with eight nodes, and it is based on a formulation that includes thickness shear deformation and does not neglect z/R in comparison with unity. The second is a 3-D rectangular prism isoparametric finite element with 20 nodes based on 3-D elasticity theory. To demonstrate the accuracy of these finite elements, a number of examples ranging from moderately thick to thick shell applications are presented and discussed with respect to thickness-to-shell radius ratios. In each example, the transitions from moderately thick shells to thick shells are calculated and compared with each other.
Keywords: moderately thick shell; finite element; three-dimensional element; thick shell; two-dimensional element